Improved protein maize from Ghana - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Even though normal maize has approximately 10% protein, this is not available to monogastric animals, including humans because the protein is low in two essenyial amino acids, Iysine and tryptophan. As a result there has been a worldwide effort to...